Gifting personal interpretations in galleries - Fosh, Lesley; Benford, Steve; Reeves, Stuart; Koleva, Boriana (ACM, 2014)
The designers of mobile guides for museums and galleries face three major challenges: fostering rich interpretation, delivering deep personalization, and enabling a coherent social visit. We propose an approach to tackling all three simultaneously by inviting visitors to design an interpretation that is specifically tailored for a friend or loved one that they then experience together. We describe a trial of this approach at a contemporary art gallery, revealing how visitors designed personal and sometimes provocative experiences for people they knew well. We reveal how pairs of visitors negotiated these experiences together, showing how our approach could deliver intense experiences for both, but also required them to manage social risk. By interpreting our findings through the lens of 'gift giving' we shed new light on ongoing explorations of interpretation, personalization and social visiting within HCI.